Identifying adverse drug events in patients at a pediatric ward in a Brazilian hospital: application and performance of the triggers - Simone Cristina Rodrigues de Carvalho Caetano; Luiz Fernando Emidio da Silva; Lusiele Guaraldo; Fabíola Giordani (Instituto Materno Infantil de Pernambuco, 2022)
Abstract Objectives: to evaluate the performance of a trigger tool in identifying adverse drug events (ADE) in hospitalized children. Methods: a retrospective cohort study review on 133 medical records at a federal maternal and child reference hospital in Rio de Janeiro in 2016. A list of 14 triggers was developed to detect ADE in the pediatric population. Three steps were performed: (1) search for triggers; (2) selection of suspected cases of ADE and (3) final determination of ADE by experts' consensus. Results: 360 triggers were identified in 100 hospitalizations (75.2%), with an average of 2.7 triggers/ hospitalization. The most frequent triggers were "abrupt medication stop" (79.7%); "antiemetics use" (8.9%) and "laxatives use" (7.2%); while the "diphenhydramine use", "phytomenadione use" and "excessive sedation/lethargy/fall/hypotension" obtained the highest performance indicating ADE every time they occurred. Thirty-one ADE were identified in 12.8% of the hospitalizations; 11 (35.5%) ADE were detected without the aid of the triggers thus, pruritus and diarrhea were the most frequent. Conclusion: the trigger tool proved to be useful in identifying ADE in hospitalized children, especially if high performance and high frequency triggers are used in identifying the events. The inclusion of the triggers "diarrhea" and "pruritus", may favor the identification of ADE in patients at pediatric wards.